Geochemistry, zircon U-Pb age and Hf isotope for the Huatugou granitoid in western Qaidam: Petrogenesis and tectonic implications - Teng, Xia; Zhang, Jianxin; Mao, Xiaohong; Wu, Yawei; Guo, Qi (Frontiers in Earth Science, 2023)
The Qaidam Precambrian block is located in the northeastern Tibetan Plateau and was intruded by numerous Ordovician-Devonian granitoids during and after the closure of the Proto-Tethys Ocean. In the past 20 years, the granitoids within early Paleozoic subduction-collision belts have been detailed investigated. However, the granitoids intruding the inner part of the Qaidam block, bearing the tectonic significance for the whole block, still need to be understood. This study presents new whole-rock geochemical and zircon U-Pb-Hf isotopic data for the Huatugou granitoids in the Qaidam Precambrian block. The investigated granitoids include granodiorite, monzogranite, biotite granite, and muscovite granite, which intruded the Precambrian basements during 451–400 Ma. The granodiorites (451±6 Ma) display adakitic geochemical features and syn-tectonic textures, and their magmas were generated by the partial melting of the lower mafic crust within a thickened continent. The muscovite granites (410±6 Ma), with negative zircon εHf(t) values of –14.5 to –10.4, were crystallized from fractionated S-type magmas, which were derived from the partial melting of ancient crustal materials. The biotite granite (410±3 Ma) and monzogranites (400±4 Ma) are high-temperature A2-type granites. The biotite granite displays positive zircon εHf(t) values of +1.7 to +5.6. Its magma was generated by the high-temperature partial melting of juvenile crustal rocks in a thinned lower crust. The monzogranites exhibit higher SiO2 contents and lower εHf(t) values, and their magmas were derived from the same source but underwent assimilation and fractional crystallization during emplacement. From the thickened to the thinned continent during 451–410 Ma, the western Qaidam block experienced a tectonic transition from compression to extension. Combined with regional geological data, this study suggests that the Qaidam block consisted of the thickened continental crust during subduction processes until the detachment of the subducted slab during the continental collision. The regional extension of the Qaidam block commenced at ~420 Ma, soon after the exhumation of ultrahigh-pressure metamorphic rocks within the northern Qaidam subduction-collision complex belt.